Decellularized Extracellular Matrix Materials for Cardiac Repair and Regeneration. Issue 5 (4th February 2019) - Bejleri, Donald; Davis, Michael E.
Abstract: Decellularized extracellular matrix (dECM) is a promising biomaterial for repairing cardiovascular tissue, as dECM most effectively captures the complex array of proteins, glycosaminoglycans, proteoglycans, and many other matrix components that are found in native tissue, providing ideal cues for regeneration and repair of damaged myocardium. dECM can be used in a variety of forms, such as solid scaffolds that maintain native matrix structure, or as soluble materials that can form injectable hydrogels for tissue repair. dECM has found recent success in many regeneration and repair therapies, such as for musculoskeletal, neural, and liver tissues. This review focuses on dECM in the context of cardiovascular applications, with variations in tissue and species sourcing, and specifically discusses advances in solid and soluble dECM development, in vitro studies, in vivo implementation, and clinical translation. Abstract : Decellularized extracellular matrix (dECM) materials are finding increasing success in cardiac therapies. dECM materials investigated for cardiac repair are derived from a variety of tissue and animal sources and are implemented in many forms such as solid scaffolds or injectable hydrogels. This review discusses recent advances in dECM technologies for cardiac repair, from in vitro analysis to implementation in animal models and translation toward the clinic.